2012
DOI: 10.1111/j.1364-3703.2012.00785.x
|View full text |Cite
|
Sign up to set email alerts
|

Melon RNA interference (RNAi) lines silenced for Cm‐eIF4E show broad virus resistance

Abstract: Efficient and sustainable control of plant viruses may be achieved using genetically resistant crop varieties, although resistance genes are not always available for each pathogen; in this regard, the identification of new genes that are able to confer broad-spectrum and durable resistance is highly desirable. Recently, the cloning and characterization of recessive resistance genes from different plant species has pointed towards eukaryotic translation initiation factors (eIF) of the 4E family as factors requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 48 publications
2
78
0
1
Order By: Relevance
“…The specificity allows the silencing of only one sequence among closely related sequences, as seen in this study, where only one isoform of eIF4E gene was effectively silenced (Figure 4B). Similar specific silencing of one isoform of eIF4E was also recently described in melon and tomato [64], [65]. The use of intron-containing self-complementary hpRNA (ihp-RNA) constructs was reported to dramatically enhance the RNA silencing efficiency up to 100% [66], [67].…”
Section: Discussionsupporting
confidence: 60%
“…The specificity allows the silencing of only one sequence among closely related sequences, as seen in this study, where only one isoform of eIF4E gene was effectively silenced (Figure 4B). Similar specific silencing of one isoform of eIF4E was also recently described in melon and tomato [64], [65]. The use of intron-containing self-complementary hpRNA (ihp-RNA) constructs was reported to dramatically enhance the RNA silencing efficiency up to 100% [66], [67].…”
Section: Discussionsupporting
confidence: 60%
“…Data on resistance breaking suggested that the new 3′‐CITE could function either with the different eIF4E variants expressed by susceptible or resistant melon, or independently of eIF4E. To learn if this new 3′‐CITE was eIF4E‐dependent, its activity in melon protoplasts of a previously described eIF4E knock‐down line was studied (Rodríguez‐Hernández et al ., ). Through expression of a hairpin construct targeting and thus silencing melon eIF4E , its expression had been shown to be reduced more than six‐fold.…”
Section: Resultsmentioning
confidence: 99%
“…drive cap-independent translation of the messenger RNAs bearing it (Nieto et al, 2006;Truniger et al, 2008;Rodríguez-Hernández et al, 2012). Briefly, this assay is based on the capacity of Cm eIF4E-WT to complement the Ma5TE-controlled translation of RNAs when it is transiently expressed in melons that carry the Cm eIF4E H228L allele in homozygosity, which does not support Ma5TE-driven translation (Nieto et al, 2006;Miras et al, 2017b).…”
Section: Testing Substitutions In CM Eif4e-binding Residues In a Tranmentioning
confidence: 99%
“…In vivo translation assays were performed as previously described (Truniger et al, 2008) by electroporating separately with two 59-UTR-luc-39-UTR RNA constructs, differing in the UTRs flanking the luciferase gene that were either from isolate MNSV-Ma5 (eIF4E-dependent) or from the eIF4E-independent isolate MNSV-264. Translation of MNSV-264 can take place in protoplasts from eIF4E knocked-down lines, so it can function in the absence of eIF4E (Rodríguez-Hernández et al, 2012) and therefore serves for normalization of the different protoplast preparations. After 5 to 6 h incubation in the dark at 25°C, protoplasts were lysed in 1x Passive lysis buffer (Promega).…”
Section: Translation Complementation By Transiently Expressed CM Eif4ementioning
confidence: 99%